2004
DOI: 10.1071/fp03236
|View full text |Cite
|
Sign up to set email alerts
|

Die and let live: leaf senescence contributes to plant survival under drought stress

Abstract: Leaf senescence is a highly regulated physiological process that leads to leaf death and is, as such, the last developmental stage of the leaf. Plant aging and environmental stresses may induce the process of senescence. Here we will focus on the role of leaf senescence in field-grown plants as a response to adverse climatic conditions and, more specifically, on how it contributes to plant survival under drought stress. Drought induces several responses in plants including leaf senescence, which plays a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
318
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(352 citation statements)
references
References 92 publications
13
318
0
3
Order By: Relevance
“…10 Increased ROS levels also induce leaf senescence, contributing to the maintenance of water balance within the whole plant and nutrient remobilization to the youngest leaves or sink organs. 11 We found that the NTL4 gene is induced in the presence of H 2 O 2 , suggesting that the NTL4 gene would be related with ROS response and/or signaling. 5 In addition, endogenous contents of ROS were altered in the 35S:4ΔC transgenic plants and ntl4-1 mutants.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…10 Increased ROS levels also induce leaf senescence, contributing to the maintenance of water balance within the whole plant and nutrient remobilization to the youngest leaves or sink organs. 11 We found that the NTL4 gene is induced in the presence of H 2 O 2 , suggesting that the NTL4 gene would be related with ROS response and/or signaling. 5 In addition, endogenous contents of ROS were altered in the 35S:4ΔC transgenic plants and ntl4-1 mutants.…”
mentioning
confidence: 91%
“…11 However, it is unknown how ROS metabolism is linked with the drought-induced leaf senescence. We found that when the pNTL4-GUS transgenic plants were exposed to water deficit, GUS activity was significantly leaf senescence was accelerated in the 35S:4ΔC transgenic plants, it was significantly delayed in the ntl4 mutants under drought conditions.…”
Section: Regulation Of Reactive Oxygen Species Generation Under Drougmentioning
confidence: 99%
“…Dramatic changes in cell structure and metabolism occur during leaf senescence, including the degradation of chloroplasts, mitochondria, and nuclei, and simultaneous catabolism of chlorophyll pigments, nucleic acids, proteins, and lipids. The nutrients released from senescing leaves are transported to newly-developing leaves, fruits, or seeds (Buchanan-Wollaston et al, 2005;Lim et al, 2007a;Munné-Bosch and Alegre, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on transgenic tobacco showed that delayed leaf senescence increases plant resistance to drought stress (1). However, the senescence and abscission of older leaves and subsequent transfer of nutrients are known to increase plant survival under abiotic stresses, including drought, low or high temperatures, and darkness (2,3). Senescence mainly develops in an age-dependent manner and is also triggered by environmental stresses and phytohormones, such as abscisic acid (ABA), ethylene, salicylic acid, and jasmonic acid, but delayed by cytokinin (4).…”
mentioning
confidence: 99%